Household Waste Management Policy in Sidoarjo Regency Post Presidential Decree Number 97 of 2017 in Indonesia: Kebijakan Pengelolaan Sampah Rumah Tangga Di Kabupaten Sidoarjo Pasca Perpres Nomor 97 Tahun 2017 di Indonesia - Kevin Garnida Putra; Rifqi Ridlo Phahlevy (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine whether Perbup Number 100 of 2018 concerning policies and strategies for Sidoarjo Regency in managing household waste and similar household waste is in line with Presidential Regulation Number 97 of 2017 concerning national policies and strategies for managing household waste and other types of household waste in Indonesia. Sidoarjo Regency and to assess the technical suitability of waste processing in Sidoarjo Regency with Perbup Number 100 of 2018 Sidoarjo Regency policies and strategies in managing household waste and waste similar to household waste. This research was conducted at the Berkah Abadi Waste Bank and Telulikur Garbage Bank. The type of this research is socio-legal with a statute approach. The results of this study state that Perbup Number 100 of 2018 concerning policies and strategies for Sidoarjo Regency in managing household waste and waste similar to household waste is in line with Presidential Regulation Number 97 of 2017 concerning national policies and strategies for managing household waste and other types of household waste in Indonesia. Sidoarjo Regency and technical waste processing in both waste banks are in accordance with Perbup Number 100 of 2018 Sidoarjo Regency policies and strategies in managing household waste and waste similar to household waste. Keywords: Waste bank, Regent Regulation, Presidential Regulation